CLINICAL ASPECTS OF UNCOMPLICATED AND SEVERE MALARIA - Alessandro Bartoloni; Lorenzo Zammarchi (Mediterranean Journal of Hematology and Infectious Diseases)
The first symptoms of malaria, common to all the different malaria species, are nonspecific and mimic a flu-like syndrome. Although fever represents the cardinal feature, clinical findings in malaria are extremely diverse and may range in severity from mild headache to serious complications leading to death, particularly in falciparum malaria. As the progression to these complications can be rapid, any malaria patient must be assessed and treated rapidly, and frequent observations are needed to look for early signs of systemic complications.